Portuguese reactions to the housing crisis: Is it possible to move from the residualisation to post-neoliberalisation of housing policies? - Pereira, S. M. (2024)
For decades, the analysis of housing policies in Portugal has focused on its distinct trajectory compared to those of other countries in western and northern Europe. However, the rise of the housing affordability crisis and the civic, media and political prominence that the housing issue has acquired in recent years have highlighted important similarities (despite some key specifics) with the dynamics that have been occurring internationally. This article discusses Portuguese political reactions to the affordability crisis. It presents a critical discussion of the ambitious multi-measure policy package ‘Mais Habitação’ (More Housing), including its content, the political conditions of its introduction, and its public reception - in the light of the recent international debates on the paths, possibilities, and obstacles to the post-neoliberalisation of housing policies.